Combined anti-tumor necrosis factor-α therapy and DMARD therapy in rheumatoid arthritis patients reduces inflammatory gene expression in whole blood compared to DMARD therapy alone - Edwards, Carl K.; Green, Julie S.; Volk, Hans-Dieter; Schiff, Michael; Kotzin, Brian; Mitsuya, Hiroaki; Kawaguchi, Tatsuya; Sakata, Ken-Mei; Cheronis, John; Trollinger, David; Bankaitis-Davis, Danute; Dinarello, Charles A.; et al. (Frontiers in Immunology, 2012)
Periodic assessment of gene expression for diagnosis and monitoring in rheumatoid arthritis (RA) may provide a readily available and useful method to detect subclinical disease progression and follow responses to therapy with disease modifying anti-rheumatic agents (DMARDs) or anti-TNF-α therapy. We used quantitative real-time PCR to compare peripheral blood gene expression profiles in active ("unstable") RA patients on DMARDs, stable RA patients on DMARDs, and stable RA patients treated with a combination of a DMARD and an anti-TNF-α agent (infliximab or etanercept) to healthy human controls. The expression of 48 inflammatory genes were compared between healthy controls (N=122), unstable DMARD patients (N=18), stable DMARD patients (N=26), and stable patients on combination therapy (N=20). Expression of 13 genes was very low or undetectable in all study groups. Compared to healthy controls, patients with unstable RA on DMARDs exhibited increased expression of 25 genes, stable DMARD patients exhibited increased expression of 14 genes and decreased expression of five genes, and combined therapy patients exhibited increased expression of six genes and decreased expression of 10 genes. These findings demonstrate that active RA is associated with increased expression of circulating inflammatory markers whereas increases in inflammatory gene expression are diminished in patients with stable disease on either DMARD or anti-TNF-α therapy. Furthermore, combination DMARD and anti-TNF-α therapy is associated with greater reductions in circulating inflammatory gene expression compared to DMARD therapy alone. These results suggest that assessment of peripheral blood gene expression may prove useful to monitor disease progression and response to therapy.